Kemandirian Belajar Mahasiswa melalui Blended Learning Berbasis Literasi Digital pada Mata Kuliah Aljabar Linier dan Matriks - Nurul Asma Aziz; Khairunnisak Khairunnisak (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
The importance of self-regulated learning in students is able to make them responsible learners, easy to solve problems, have certain strategies in acquiring knowledge, and control themselves in thinking and acting. Blended Learning is a method that combines conventional learning with virtual learning. The various features presented via the internet can make students active and independent in looking for reference sources as literature to develop their knowledge. The aim of this research is to determine the learning independence of students who take lectures using Blended Learning based on digital literacy. The research method used is a qualitative method. Data analysis was carried out by processing student response questionnaire data and calculating the percentage of response scores to the ideal score. The results obtained were that on average respondents gave the option of agreeing with the highest percentage, namely 45%. Meanwhile, the percentage result of the respondent's response score was 83%, which shows that the respondent's response was in good criteria, because it had a range between 68.01–84.00. So it can be concluded that learning through digital literacy-based Blended Learning has a positive impact on student learning independence.